Gender Differences in the Willingness to Compete Emerge Early in Life and Persist - Sutter, Matthias; Glätzle-Rützler, Daniela (Management science, 2015)
Gender differences in the willingness to compete have been identified as one important factor in explaining gender differences in labor markets and within organizations. We present three experiments with a total of 1,570 subjects, ages three to 18 years, to investigate the origins of this gender gap. In a between-subjects design we find that boys are more likely to compete than girls as early as kindergarten and that this gap prevails throughout adolescence. Re-examining the behavior of 316 subjects in a within-subjects design two years later, we show that these gender differences also largely persist over a longer time period and can thus be considered stable. Controlling for subjects' abilities in the different tasks, their risk attitudes, and expected performance, the gender gap in the willingness to compete is estimated in the range of 10–20 percentage points. We discuss the implications of our findings for policy interventions and organizational management. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.1981 . This paper was accepted by Uri Gneezy, behavioral economics.